Vestibular Disorders and Their Impact on Balance and Mobility - Shahid Majeed, Samina Farooqi, Anum Jamshed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Our sense of balance and spatial orientation is reliant on intricate network of structures in the inner ear called the vestibular system. Any disruption or damage to this system can result in various vestibular disorders that significantly affect an individual’s balance and mobility. Objectives: The study highlighted the impact of vestibular disorders on balance and mobility of the body, its importance of early detection and outcome. Methods: The research was conducted at Mufti Mehmood Memorial Teaching Hospital, Dera Ismail Khan, from September 2021 to December 2022, comprising 86 participants having trouble in body balance and mobility diagnosed with vestibular disorders. They were investigated though a balance questionnaire including questions about their history of dizziness and falls for 01 year and a balance test through modified Romberg Test. Results: Mean age of patients was 54.22+10.47 years. It was seen that out of 86 patients, 17 had a history of falling (19.76%), 23 (26.74%) reported experiencing dizziness, 63 (73.26%), 8 (9.3%) patients reported having a history of fainting, while 38 (44.18%) reported mild vertigo, 13 (15.11%) reported moderate vertigo, and 7 (8.13%) reported severe vertigo. The impact of vestibular disorders on balance and mobility measured through Modified Romberg Test revealed that only 15 (17.44%) patients passed Romberg Test and 71 (82.55%) were failed and ranked positive cases for loss of body balance and mobility. Practical implication: Overall, research on vestibular disorders and their impact on balance and mobility has important practical implications for healthcare providers and patients. Early detection, targeted interventions, education, assistive devices, and a multidisciplinary approach can all help improve balance and mobility and reduce the risk of falls. Conclusion: Vestibular disorders can have a significant impact on an individual’s balance and mobility. The presence of vestibular dysfunction significantly raises chances of falls, which are among the most debilitating and expensive health conditions affecting elderly individuals. Keywords: Fall injuries; Romberg test; Vertigo; Vestibular dysfunction.